1995
DOI: 10.1080/10610279508029886
|View full text |Cite
|
Sign up to set email alerts
|

The influence of phenyl substituents on the redox potentials of sterically hindered tripodal ligand/copper complexes

Abstract: The structural characterization of Cu(1) and Cu(I1) complexes of tris(6-phenyl-2-pyridylmethyl)amine (tppa), a derivative of the known tris(2-pyridylmethy1)amine (tpa), was recently reported. The phenyl substituents in [Cu(tppa)AN](CIOJ, stabilize the Cu(1) state by 300-480 mV relative to [Cu(tpa)AN](CIO,),. Reported here is the synthesis of the compounds bis(2-pyridylmethyl)-6-phenyl-2-pyridylmethylamine (Phtpa) and bis(6-phenyl-2-pyridylmethyl)-2-pyridylmethylamine (Ph,tpa) and the synthesis and cyclic volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 26 publications
6
39
0
Order By: Relevance
“…[28,38] For each complex, the spectral data is consistent Cyclic voltammetry studies of 30 revealed that in various solvents the redox potential of this complex is positive (up to several hundred mV) relative to that of [(TPA)Cu(NCCH 3 )](ClO 4 ) 2 . [21,27] The more positive potential of 30 may be related to electron withdrawing effects of the phenyl substituents, or a reduction in the local dielectric due to steric shielding of the copper center by the phenyl groups. This shielding may limit access of a polar solvent to the metal center.…”
Section: Chemistry Of Aryl-appended Tpa Ligands 137mentioning
confidence: 98%
See 4 more Smart Citations
“…[28,38] For each complex, the spectral data is consistent Cyclic voltammetry studies of 30 revealed that in various solvents the redox potential of this complex is positive (up to several hundred mV) relative to that of [(TPA)Cu(NCCH 3 )](ClO 4 ) 2 . [21,27] The more positive potential of 30 may be related to electron withdrawing effects of the phenyl substituents, or a reduction in the local dielectric due to steric shielding of the copper center by the phenyl groups. This shielding may limit access of a polar solvent to the metal center.…”
Section: Chemistry Of Aryl-appended Tpa Ligands 137mentioning
confidence: 98%
“…The Cu(II) complexes [(6-Ph 2 TPA)Cu(NCCH 3 )](ClO 4 ) 2 and [(6-PhTPA)Cu(NCCH 3 )](ClO 4 ) 2 were prepared to further examine how the hydrophobic phenyl appendages influence the electrochemical properties of the copper center in acetonitrile solution. [27] These studies revealed that each phenyl substituent imparts approximately a 100 mV increase in the redox potential of the metal center.…”
Section: Chemistry Of Aryl-appended Tpa Ligands 137mentioning
confidence: 98%
See 3 more Smart Citations